A cage for thinking people - Borek, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2021)
Andrzej Dragan’s book Quantechism or a cage for people is a great popular science book to start a fascinating adventure with the theory of relativity and quantum mechanics. It is written in an easy language, does not require from the reader a deep knowledge of contemporary physical issues, while describing, illustrating and explaining them very well. Instead, it requires broader historical knowledge and at least basic philosophical knowledge for verification, helping to bring out what is most valuable in the book. Unfortunately, the book, while popularizing science, also makes a terrible mess and does a lot of damage to the deeper understanding of physics, its history, and the meaning and function of philosophy and religion. And so it can become an attractive and appealing, but nevertheless a trap-cage for thinking people.